Having a Say: 'Access to Justice' as Democratic Participation - Jennifer Leitch (UCL Journal of Law and Jurisprudence, 2015)
Despite the pervasiveness of civil law in Western societies and the impact of itsjudicial creation and administration, citizens are too often bystanders in litigation; they areeither represented by lawyers, and/or increasingly required to resolve these problemsthemselves without the assistance of legal representation. In terms of access to justice policyand initiatives, the response to this critical problem represents one of the most contestedissues on the law-and-society agenda and there have been continuing debates over themeaning of access, its objectives, and its success. The question that arises in this regard ispertinent – can access to justice initiatives empower individuals to meaningfully participate inthe legal decisions and processes that affect their lives and by extension, the democraticprocess? This paper critically examines whether, given the structure of the civil justicesystem, participation by self-represented litigants is a legitimate or viable foundation foraccess to justice initiatives. >> Read full article